The Implementation of Distance-Angle Signature as Object Shape Identifier for Digital Images - Andika Setiawan; Rajif Agung Yunmar (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
The transformation of objects in computer graphics is very closely related to the factor of scale and rotation. Both are often a challenge in the introduction of objects through numerical features in digital images. Feature processing techniques that can overcome these problems such as Distance - Angle signature that is invariant to the scale and rotation factor. From the results of experiments conducted on 5 types of geometric shape images which amounted to 15 data with scale and rotation factors obtained the results that the Angle Signature can be applied well on all data. Inequality in the signature plot images obtained is due to the lighting conditions and background objects that are not uniform, which occurs in the image of a circle for all three types.